A human milk oligosaccharide prevents intestinal inflammation in adulthood via modulating gut microbial metabolism - Schalich, Kasey M.; Buendia, Matthew A.; Kaur, Harpreet; Choksi, Yash A.; Washington, M. Kay; Codreanu, Gabriela S.; Sherrod, Stacy D.; McLean, John A.; Peek, Jr, Richard M.; Acra, Sari A.; Townsend, Steven D.; Yan, Fang (mBio, 2024)
At present, neither basic research nor clinical studies have revealed the exact biological functions or mechanisms of action of individual oligosaccharides during development or in adulthood. Thus, it remains largely unknown whether human milk oligosaccharides could serve as effective therapeutics for gastrointestinal-related diseases. Results from the present study uncover 2′-FL-driven alterations in bacterial metabolism and identify novel B. infantis -secreted metabolites following the consumption of 2′-FL, including pantothenol. This work further demonstrates a previously unrecognized role of pantothenate in significantly protecting the intestinal barrier against oxidative stress and mitigating colitis in adult mice. Remarkably, 2′-FL-enhanced bacterial metabolic pathways are found to be dysregulated in the fecal microbiota of ulcerative colitis patients. These novel metabolic pathways underlying the bioactivities of 2′-FL may lay a foundation for applying individual oligosaccharides for prophylactic intervention for diseases associated with impaired intestinal homeostasis.